Emergency Department Revisits Due to Cast-Related Pain in Children with Forearm Fractures - Kvatinsky N; Carmiel R; Leiba R; Shavit I (Journal of Pain Research, 2020)
Noa Kvatinsky,1 Rivka Carmiel,2 Ronit Leiba,3 Itai Shavit1 1Pediatric Emergency Department, Rambam Health Care Campus, Haifa, Israel; 2Rappaport Faculty of Medicine, Technion-Israel Institute of Technology, Haifa, Israel; 3Quality of Care Unit, Rambam Health Care Campus, Haifa, IsraelCorrespondence: Itai Shavit POB 274, Kibutz Maayan Tzvi, Haifa 3080500, IsraelTel +972-50-2063239Fax +972-4-777-4012Email itai@pem-database.orgBackground: Cast immobilization is the primary treatment for children with forearm fractures. After emergency department (ED) discharge, some patients develop cast-related pain (CstRP) around the distal part of the upper extremity. We examined variables associated with ED revisits due to CstRP in children with forearm fractures.Methods: A retrospective cohort study of all children who were treated with cast immobilization for forearm fracture over a 7-year period was conducted. Patient demographics, fracture location, casting method (below elbow/above elbow), first visit pain scores, treatment with fracture reduction, and revisit data were collected. Multivariate regression was used to identify predictors of revisits due to CstRP within 72 hrs post-discharge.Results: A total of 2307 children were treated with cast immobilization; 95 (4.2%) revisited the ED due to CstRP (median pain score 7, interquartile range 5–9). No patient had neurovascular compromise or required surgery or re-reduction. Fifty-eight (61.1%) patients were treated with cast splitting, 10 (10.5%) with trimming, and 27 (28.4%) with cast replacement. Variables on first visit that were associated with increased odds for ED revisit included treatment with fracture reduction (odds ratio [OR] 2.31; 95% confidence interval [CI] 1.58–3.36) and a median pain score of 6 or more upon ED presentation (OR 1.57; 95% CI 1.32–2.13).Discussion: A small number of children with forearm fractures revisited the ED due to CstRP. Study findings suggest that being treated with closed reduction and having a pain score ≥ 6 on the first visit were associated with ED revisit due to CstRP.Keywords: child, fracture, casting, pain